KARAKTERISTIK ADSORPSI TEMBAGA (II) PADA HUMIN DALAM MEDIUM AIR TAWAR - Roy Andreas; Narsito Narsito; Sri Noegrohati (Universitas Jenderal Soedirman, 2006)
Although humic substances consist mosly of humin (65%), however its characteristic in Cu(II) odsorption is not yet clearly revealed. In this work, humin was isolated from peat soil of west Kalimantan, purified and then interacted with Cu(II). The purity of isolated humin was determined by its ash content. The funtional group in this purified humin was characterized qualitatively by FTIR and quantitatively by titration. Study on the solubility of Cu(II) in freshwater was carried out at pH from 2-12 in the presence and without purified humin. To obtain adsorption kinetic parameters of Cu(II) on humin in freshwater, study based on Langmuir-Hinshelwood was carried out, while for its thermodinamics parameters, a study based on Langmuir and Freundlich were employed.The ash content of purified humin was 1,58 % (w/w), it showed that the humin was in pure condition. The active fungtional group identified humin were –COOH (1700 cm-1) 115 cmol/kg and –OH fenolic (3421,5 cm-1) 562 cmol/kg. At 2<pH<5 was in Cu(II) and [Cu(H2O)4]2+ which soluble in water, at 6<pH<7 part of the soluble Cu(II) precipitated as Cu(OH)2 while at pH>7 all of Cu(II) was precipitated as Cu(OH)2. The rate constant for Cu(II) in freshwater medium were 2,7 x 10-3 S-1 and 0,6 x 10-3 S-1. The obtained curve fitting of langmuir and freundlich adsorption showed that Langmuir model fit better than Freundlich, indicated that the adsorption reaction are of monolayer. The adsorption capacities of Cu(II) on humin in freshwater was 3,033 x 10-4 mol/g